Single-stage resection of uterine fibroids and intravascular leiomyomatosis: a case report - Jing-Xiao Li; Wei-Qi Zhang; Chao-Hai Lv; Jian-Lin Wen; Chun-Lou Wei; Jing Qian; Xiao-Chun Zeng; Liu-Liu Huang; Bao-Shi Zheng; Hua-Fu Zhou; Ting Zhou (BMC, 2024)
Abstract Background Uterine Fibroids (UFs) are common benign tumors in the female reproductive tract, but their progression to intravascular leiomyomatosis (IVL) is rare. Presently, there are few reports on single-stage resection of UFs and IVL. Case presentation A 47-year-old woman, G2P2, had been diagnosed multiple UFs four years ago and now developed heart failure. Imaging examinations revealed that UFs had invaded the right iliac vein and extended into the right atrium through the inferior vena cava. Through multidisciplinary collaboration and a single-stage resection, the patient has survived for over 24 months post-surgery, and her heart function has significantly improved compared to preoperative levels, with no recurrence of UFs observed. Conclusions Single-stage resection of IVL and UF is feasible and advantageous for this case, and selecting the appropriate surgical approach is crucial.